Epidemiology of systemic hypertension in dogs - SANGWAN, TANVIKA; SAINI, NEETU; TURKAR, SUJATA; CHHABRA, SUSHMA (The Indian Journal of Animal Sciences, 2024)
The present study was designed with the objective to evaluate the systolic BP using Doppler sphygmomanometer in healthy and clinically ill dogs and to establish the association of BP with various factors like age, sex, breed and body weight/body condition score (BCS) as well as with different disease conditions. A total of 198 dogs (46 healthy and 152 clinically ill) were enrolled in the study and it was found that mean systolic BP of apparently healthy (n=46) and clinically ill dogs (n=152) varied significantly. The average systolic BP among the diseased dogs was significantly greater in the large breed dogs (n=124) than small-medium breeds (n=74). The Pearson’s correlation coefficient revealed that age of the animals was positively correlated with BP along with a negative correlation of BCS with BP. The linear regression analysis also depicted that BCS had a significant effect on the systolic BP indicating that decreasing BCS had 13.52 times increasing systolic BP. The large breeds and male animals had more BP than the small breeds and females. The dogs affected with chronic kidney disease (CKD) had a highest prevalence of systemic hypertension indicating the more occurrence of secondary nature. Therefore, it was concluded that male dogs of large breeds affected with CKD and lower BCS had more prevalence of secondary systemic hypertension.